Compliance, noncompliance, and the in-between: causal effects of civilian demeanor on police officers’ cognitions and emotions - Nix, Justin (Journal of experimental criminology, 2019)
Police legitimacy can hinge on what happens in police-civilian encounters, yet much remains unknown about the socio-psychological processes involved in these bilateral interactions, especially those affecting officers. We integrate insights from policing research with theories and findings from scholarship on moral psychology, interpersonal strain, and victimization fear to develop hypotheses about the situational effects of civilian demeanor on officers’ cognitions (suspicion and perceived danger) and emotions (anger, frustration, annoyance, and fear).